Harry Callahan [videoreccording] a need to see and express. ([S.l.] Silver Productions, 1982)
The wide range of subjects and variety of techniques found in Callahan's photography are explored. Includes over 300 photographs plus rare footage from his films.
Keywords: Callahan, Harry; Photography; Art studies; Humanities; Fine arts